2010
DOI: 10.1007/s11162-010-9193-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gaps in Collegiate Teaching Style: Variations by Course Characteristics

Abstract: Using data from over 9,000 faculty members that participated in the Faculty Survey of Student Engagement (FSSE), this study examined the moderating role a range of course characteristics played on the effects of gender on the percentage of class time spent on various activities, a measure of teaching style. Results revealed gender differences, but that the gaps between men and women in lecturing and active classroom practices varied by disciplinary area, course level, and the number of times a course had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Some studies have pointed out that this gender effect depends on the environment. Although teachers may have personal preferences for a certain teaching method, when influenced by external stimuli, the teaching style status will adapt to the changes of the outside world (Nelson Laird et al, 2011). Women in high warmth teaching styles increased perceived warmth but also decreased perceived ability (Burnell et al, 2018), and women were more sensitive to behavioral disengagement and social support (Popa-Velea et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have pointed out that this gender effect depends on the environment. Although teachers may have personal preferences for a certain teaching method, when influenced by external stimuli, the teaching style status will adapt to the changes of the outside world (Nelson Laird et al, 2011). Women in high warmth teaching styles increased perceived warmth but also decreased perceived ability (Burnell et al, 2018), and women were more sensitive to behavioral disengagement and social support (Popa-Velea et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have pointed out that this gender effect depends on the environment. Although teachers may have personal preferences for a certain teaching method, when influenced by external stimuli, the teaching style status will adapt to the changes of the outside world (Nelson Laird et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that women may be significantly more open to new pedagogical approaches, are more knowledgeable about active learning strategies, and therefore more likely to adopt them than their male counterparts (Henderson et al 2012;Williams 2015). Further research into the reason for the gender gap in atmospheric science is needed, as well as an investigation of any learning differences that arise due to different pedagogies (Nelson Laird et al 2011).…”
Section: Gendermentioning
confidence: 99%
“…In addition, teachers may act as role models for their students (see, among others, Carrington and Skelton, 2003;Gray and Leith, 2004;Holmlund and Sund, 2008). In regards to the second kind of results, students assigned to female teachers perform better since female teachers tend to be more supportive, provide a more positive classroom atmosphere, and tend to use a more student-oriented style of teaching stressing the importance of motivation (see Stake and Katz, 1982;Singer, 1996;Krieg, 2005;Nelson Laird, 2011). Below we summarize some of the existing evidence for primary and secondary education (middle and high school).…”
Section: Introductionmentioning
confidence: 99%